Clinical profile of dengue fever in a tertiary care centre in North Kerala - K., Ramesan; M. K., Ajith Kumar; Valliyot, Balakrishnan; Balakrishnan, Sudha (International Journal of Research in Medical Sciences, 2017)
Background: Dengue fever is the most common arboviral disease and fifty percent of world population is at risk. Frequent outbreaks are reported from all states of our country and incidence increases every year. This case study is of 305 patients from Academy of Medical Sciences, which is a tertiary care centre and research Institute in North Kerala. The objective of this study was to study the clinical profile of dengue fever. Methods: Study was prospective observational study conducted during the epidemic for a period of one year. All the cases which fulfilled WHO criteria for diagnosis of dengue fever and those who are positive for IGM antibody detected by enzymelinked immunosorbent assay (IgM ELISA) were only included in this study. Results: There is male preponderance, and those above the age of 30 years affected more. All patients had fever. Gastrointestinal manifestation like nausea and vomiting were commonly observed symptoms. Hepatomegaly, rash and conjuctival suffusion were important physical findings, whereas splenomegaly noted only in 8.2% cases. Thrombocytopenia is noticed in 73.96%. Conclusions: The mortality is 2.6%. Hypotension and thrombocytopenia are the two important determinants of mortality. Dengue Shock syndrome and Dengue Hemorrhagic Fever were relatively less when compared to other epidemics from different regions.